2006
DOI: 10.1038/sj.jcbfm.9600292
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H Fluorescence Transients after Synaptic Activity in Brain Slices: Predominant Role of Mitochondrial Function

Abstract: Excitatory stimulation in hippocampal slices results in biphasic NAD(P)H fluorescence transients. Previous studies using differing stimulus protocols agreed that the oxidation phase is a consequence of mitochondrial metabolism, but the reduction phase has been attributed to (1) mitochondrial nicotinamide adenine dinucleotide (NADH) generation or (2) astrocytic glycolysis triggered by glutamate uptake. In an attempt to reconcile these two views, the present study examined NAD(P)H signals evoked by a wide range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(127 citation statements)
references
References 53 publications
8
115
4
Order By: Relevance
“…The decrease in basal NADH fluorescence during hypoglycemia reflects a reduction in the potential for ATP regeneration but in the presence of normal oxygen levels, in effect forcing most of the NADH to NAD. Brennan et al demonstrated that an adenosine A1 receptor antagonist could alleviate 2-deoxyglucose (chemical hypoglycemia) induced attenuation of the biphasic NADH response to a stimulus train [5]. We also found that glucose concentrations modulate the second phase of the NADH biphasic response, which may reflect impaired recovery of mitochondrial energy intermediates in the lowered glucose media [25,39].…”
Section: Nadh Measurementssupporting
confidence: 62%
“…The decrease in basal NADH fluorescence during hypoglycemia reflects a reduction in the potential for ATP regeneration but in the presence of normal oxygen levels, in effect forcing most of the NADH to NAD. Brennan et al demonstrated that an adenosine A1 receptor antagonist could alleviate 2-deoxyglucose (chemical hypoglycemia) induced attenuation of the biphasic NADH response to a stimulus train [5]. We also found that glucose concentrations modulate the second phase of the NADH biphasic response, which may reflect impaired recovery of mitochondrial energy intermediates in the lowered glucose media [25,39].…”
Section: Nadh Measurementssupporting
confidence: 62%
“…[38][39][40][41] This in vitro preparation also provides a reasonable model for examining energy metabolism during different forms of neuronal network activation. [42][43][44][45] In the hippocampal slices, persistent gamma oscillations can be reliably induced by bath application of cholinergic or glutamatergic receptor agonists at nanomolar to low micromolar concentrations ( Figures 1A and 1B). The most widespread models use acetylcholine or carbachol for activation of metabotropic cholinergic receptors, or kainate (kainic acid) for activation of ionotropic glutamatergic receptors.…”
Section: Gamma Oscillations and Cortical Information Processingmentioning
confidence: 99%
“…10,11 We applied pharmacology to dissect single components contributing to the enhanced energy consumption. Figures 3A--3E, n ¼ 5, 13, 13).…”
Section: Energy Demand Associated With Pre-and Postsynaptic Ion Fluxesmentioning
confidence: 99%